Agri-photovoltaic and agriculture machine vision AI: AI-MV for yield prediction, growth forecasting in precision agriculture - Sng, Ryan Wei Quan (Nanyang Technological University, 2024)
Advanced technologies such as indoor hydroponics systems and vertical farms have emerged as potential solutions to address food security challenges. These systems create optimal growth environments, leveraging on artificial lighting, effectively maximizing crop yield while minimizing the need for extensive land space and natural lighting. However, these benefits come at the expense of increased energy consumption.